Spectroscopic studies of plasma streams generated in a 1-MJ plasma-focus facility with and without gas-puffing - Ladygina, M.S.; Skladnik-Sadowska, E.; Kwiatkowski, R.; Malinowski, K.; Sadowski, M.J.; Zaloga, D.; Żebrowski, J.; Kubkowska, M.; Paduch, M.; Scholz, M.; Zielinska, E.; Makhlaj, V.A. (Вопросы атомной науки и техники, 2015)
The main aim of the reported experimental session was to study operational characteristics of a modified PF-1000U facility during a free propagation of a plasma-stream and its interactions with a carbon-fiber composite (CFC) target. The facility was equipped with an axial fast-acting valve for additional gas puffing into a region close to the electrodes outlets. Experiments were carried out with and without the gas puffing in chosen instants before the application of high voltage pulse. The operational regimes of the facility were established by changing these parameters and the initial charging voltage. To record optical spectra of the plasma radiation the use was made of a Mechelle®900 spectrometer coupled with a CCD-camera sensitive in a wavelength range of 300...1100 nm. During all reported experiments the exposition time was equal to 100 ns, but a time delay was changed to obtain data for different discharge phases. The performed spectral measurements enabled to study plasma dynamics, to identify plasma impurities, and to estimate electron densities and temperatures. The electron density in a free-propagating plasma stream was calculated from a linear Stark-effect observed for the Dα spectral line. Главной целью докладываемой экспериментальной сессии было изучение рабочих характеристик модифицированной установки PF-1000U во время свободного распространения плазменного потока и его взаимодействия с углеродной мишенью CFC. Установка была переоснащена специальным быстро действующим клапаном для дополнительного напуска газа в зону фокуса (область, близкую к концам электродов). Эксперименты проводились c импульсным напуском и без напуска газа в выбранные моменты времени до применения импульса высокого напряжения. Рабочие режимы установки PF-1000U определялись изменениями этих параметров и начального зарядного напряжения. Чтобы зарегистрировать оптические спектры плазменного излучения использовался спектрометр Mechelle®900 с подсоединенной к нему CCD-камерой, чувствительной в диапазоне 300…1100 нм. Во время всей серии экспериментов время экспозиции было равно 100 нс, но время задержки спектрометра изменялось для получения данных в различные фазы разряда. Выполненные спектральные измерения касались динамики плазмы, идентификации примесей в плазме, так же как и оценок электронной плотности и температуры. Электронная плотность в свободном плазменном потоке рассчитывалась из линейного штарк-эффекта, наблюдаемого для спектральной линии Dα. Основною метою в експериментальній сесії, що доповідається, було вивчення робочих характеристик модифікованого пристрою PF-1000U під час вільного розповсюдження плазмового потоку та взаємодії з вуглецевою мішенню CFC. Установка була обладнана спеціальним швидким клапаном для додаткового напуску газу в зону фокусу (область, близька до кінців електродів). Експерименти проводились без напуску та з напуском газу до подачі високої напруги. Робочі режими визначались змінами цих параметрів та початкової зарядної напруги. Для того, щоб зареєструвати оптичні спектри випромінювання плазми використовувався спектрометр Mechelle®900 із CCD-камерою, чутливою в діапазоні довжин хвиль 300…1100 нм. Під час всієї серії експериментів час експозиції був 100 нс, але час затримки спектрометра змінювався, щоб отримати дані в різні фази розряду. Проведені спектральні вимірювання стосувались динаміки плазми, ідентифікації домішок у плазмі, так як і оцінок плазмової густини та температури. Електронна густина у вільному плазмовому потоці розраховувалась з лінійного штарк-ефекту, що спостерігався для спектральної лінії Dα.